Different modalities in diagnosis of thrombotic pulmonary embolism: a hospital-based study - Ibrahim M Shalan; Hosni A Younis; Haitham A Azeem; Mohamed Mahmoud; Saad R Abdulwahed Hussein (Wolters Kluwer Medknow Publications, 2018)
Background Pulmonary embolism (PE) is a potentially life-threatening cardiovascular emergency with a high mortality rate; PE is a difficult diagnosis that may be missed because of nonspecific clinical presentation. However, multidetector computed tomography pulmonary angiography (MDCT-PA) is considered the gold standard in diagnosis. D-Dimer has high sensitivity to PE that if negative and clinical probability is low PE can safely be excluded without the need for further investigation. Objective The aim of this study was to evaluate demographic data, clinical, radiographic, and laboratory findings in patients with PE and the relationship of those findings with the embolism location, and the reason for severity of the embolism. Patients and methods This study was conducted on 100 patients diagnosed with PE based on MDCT-PA at Chest Diseases Department of Al-Azhar Assiut and Assiut University Hospitals, Egypt, from May 2013 to December 2015. All patients were subjected to complete history taking, clinical examination, routine investigations, D-dimer, O2 saturation, arterial blood gases, ECG, Doppler ultrasound, chest radiography, MDCT-PA for all patients, and echocardiography in selected patients. Results There were significant differences between D-dimer from one hand and severity of PE, and also the site and extent of the embolus from the other hand, as D-dimer levels were higher in massive than submassive PE, and in main pulmonary artery embolus than segmental branches, and lastly subsegmental branches. ECG findings in PE were nonspecific but could aid in the diagnosis. The most common findings were sinus tachycardia followed by inverted T wave in anterior chest leads, whereas the typical S1Q3T3 was less common. Conclusion A practical and evidence-based approach is to combine a D-dimer result with a validated clinical risk score to help selection of suitable patients for computed tomography pulmonary angiogram. Recommendation A clinical probability assessment and D-dimer value should be combined and used to quantify the patient's risk of PE as low, moderate, or high.